P216 Local Endobronchial Ultrasound (ebus) Service Reduces Waiting Time For Test Results. (10th November 2014) - Dickson, JL; Lawson, M
Abstract : Introduction: Endobronchial ultrasound (EBUS) is increasingly used in investigating mediastinal lymphadenopathy. A recent Thorax paper suggested EBUS should only be performed in large centres to ensure quality. A recently established EBUS service at Broomfield Hospital appeared to reduce the time taken to obtain results compared to the regional service previously used. The service was audited to ensure quality and evaluate changes to pathway times. Objectives: Compare time from decision for EBUS to test result between local and regional service and ensure safety and accuracy. Methods: Data were collected prospectively for all EBUS cases after the local service was established in August 2013. Accuracy and safety of the service were audited based on the first 8.5 months of operation. Data were extracted from the MDT database for patients referred to the regional service between November 2013 and January 2014. Time from MDT decision for EBUS referral and subsequent MDT discussion of results were compared between both services. Data were compared using the Mann-Whitney U test using the statistics package in R. Results: Average time from decision to EBUS result was 19 days in the local service based on the first 21 cases performed. There was a 40 day average turnaround for the regional service based on the 10 cases referred between November 2013 and January 2014. This represented a statistically significant reduction in waiting time of 21 days (p = 0.0001). The local service was safe and accurate with no reported complications in 42 cases over the first 8.5 months and an overall accuracy of 88% increasing to 94% (31/33) in suspected cancer cases. Conclusions: Our recently established local EBUS service is safe and accurate but also significantly reduces the time between decision to EBUS and test results discussed in MDT compared to the regional referral service previously used. This is important for patients on the 62-day cancer pathway. A local service enables people to undergo investigations nearer to home. The establishment of national reference standards for EBUS is important to ensure optimal quality but this can be achieved in local services which may offer additional benefits to patients.